Screening of advanced sugarcane genotypes against rust mite - K S, MOHAN KUMAR; SHARMA, KULDEEP; VIJAYKUMAR, L; YADAV, SURESH (The Indian Journal of Agricultural Sciences, 2021)
In the screening trial, among the nineteen sugarcane genotypes screened for the reaction to sugarcane rust mite, Abacarus sacchari, only 2 genotypes (009-64 and 0961-07) harboured >1 mites /2 cm2 leaf area while remaining all the genotypes harboured <2 mites/2 cm2 leaf area for the entire crop duration. Morphological characters of genotypes revealed that interveinal distance, leaf area and trichome density were found to influence the A. sacchari negatively. The genotype with high phenol and lower amount of total sugar, reducing sugar, crude protein was found with the lower level of incidence of mites. The study on the role of leaf nutrient on the mite population revealed that genotype with higher potassium content and lower nitrogen levels were found with the minimum incidence of A. sacchari.